Alejandro Ortega Hernández, Ramos Montalvo Vargas, María de Lourdes Cárcamo Solís y Gustavo E. Rojo Martínez (coord). 2012. Agricultura y Migración en el Occ idente de México. Editorial Panorama, IS BN: 978-607-7673-34-7. - Cárcamo-Solís, María de Lourdes (Agricultura, Sociedad y Desarrollo, 2013)
The link between agriculture and migration is approached in this book, as a phenomenon that has been accentuated by the absence of agrarian policies that drive the sustained development of peasant agriculture. This type of agriculture has been historically in a persistent crisis that has still not been resolved by structural reforms, whose â€œescape valveâ€ â€“as pointed out by Estuardo Lara Ponce in the Prologueâ€“ is migration as an alternative source of income for survival and to alleviate potential social and political tensions.